PENGARUH PENDIDIKAN KELUARGA TERHADAP MASA DEPAN ANAK - Gurning, Lasmauli (JURNAL KADESI, 2023)
Education is an effort consciously undertaken to prepare the student through guidance, teaching, and/or training activities for his/her role in the future. The education a child acquires not only in school, but also in the family.The family is the first reservoir or place of education for a child. The purpose of the research is as a reference to enrich the study of literature on the influence of family education on the future of the child. Thus the family in this case parents understand and understand their duty in the upbringing of children. The type of research that is used in this study is library research, which is the kind of research which limits its activity to library materials that do not do field research. It is the duty of parents to educate, guide and educate in the life of this world and the Hereafter. And it's from parents that children first know the world. Through them the child develops the whole aspect of his personality. In this case, parents not only give birth to children, but also give education and knowledge and affection to children. Family education plays an important role in the future of the child.